Increasing the Knowledge and Skills of Housewives through Training in Making Chocolate Banana Chips in Bayeman Village - Fitri Kurnia; Hani Nafi’ah Rachmawati; Rosida; Nur Khosiah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aimed to assess the effectiveness of chocolate banana chip-making training in improving the knowledge and skills of housewives in Bayeman Village. It also emphasizes the importance of such training in empowering housewives to contribute to family finances. With enhanced knowledge and skills in chocolate banana chip production, it is expected that housewives can produce high-quality products competitive in local and regional markets. A qualitative descriptive approach was used to outline the training program conducted during the Real Work Lecture in Bayeman Village. The training and counseling activities in the KKN program aim to increase the market value of products in the village. The implications of the study underscore the need for local authorities and relevant institutions to organize more similar training sessions to enhance the economic independence of rural communities. This, in turn, can lead to local economic development by empowering housewives. Additionally, further research is needed to evaluate the sustainability of this training, including the retention and application of acquired knowledge and skills by housewives in Bayeman Village in the long run.